Combined geochemical and geochronological analyses of stone artefacts provide unambiguous evidence of intra- and inter-island interactions in Polynesia. (June 2017) - Hermann, Aymeric; Sauzéat, Lucie; Guillou, Hervé; Maury, René C.; Chauvel, Catherine; Liorzou, Céline; Conte, Eric
Abstract: Stone tool geochemistry provides hard evidence for post-settlement voyaging and inter-island contacts in East Polynesia. This offers promising information on inter-community exchange networks that are not documented by ethnographic accounts. Drawing on "geochemical fingerprints", provenance studies have slowly integrated geological data in order to better constrain the origin of archaeological material. However, the occurrence of overlapping geochemical signatures within Polynesian islands can cause difficulties when attempting to differentiate sources. Identifying clear geochemical characteristics for each island is therefore critical for a comprehensive understanding of the interaction patterns in East Polynesian societies. In this paper, we combine major and trace element data with isotopes as well as 40 Ar- 39 Ar ages to constrain the local procurement networks that were occurring on the island of Tupua'i (Austral-Cook chain). We also demonstrate that some Tupua'i archaeological material originated from Eiao Island (Marquesas chain) circa 2000 km north. This represents the first hard evidence for inter-island connections between the Austral and the Marquesas Archipelagos. Highlights: New geochronological technique used to establish the provenance of stone artefacts Combining geochemistry and geochronology improves sourcing of basaltic artefacts A geological setting for Central Eastern Polynesia is defined Procurement networks for adze production in Tupua'i (Austral Islands) are described Long-distance exchange is evidenced between the Marquesas and the Austral Islands